Teacher Strategies for Developing Elementary Students’ Tolerance through Pancasila Education - Antonius Remigius Abi (Jurnal Pendidikan, Media, Strategi, dan Metode., 2026)
Tolerance is an essential character value in elementary education because students need to learn how to respect differences, listen to others, cooperate with peers, avoid ridicule, and accept diverse opinions, habits, and backgrounds. Pancasila Education provides a strategic space for developing tolerance because it introduces students to values of humanity, unity, mutual respect, and responsible citizenship. This study aimed to describe teachers’ strategies in developing students’ tolerance attitudes through Pancasila Education learning in elementary school. The study employed a descriptive qualitative approach. The main informant was a class teacher or Pancasila Education teacher, while supporting informants consisted of the principal and five students. Data were collected through classroom observation, interviews, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing. Data validity was strengthened through triangulation of observation, teacher interview, student interview, and documentation. The findings revealed seven major themes: integration of tolerance values in lesson planning, active and contextual learning strategies, teacher modeling, habituation of tolerance through classroom interaction, reinforcement of Pancasila values, obstacles in tolerance attitude formation, and teacher solutions. The teacher developed tolerance by inserting tolerance values into learning objectives, learning materials, classroom activities, case examples, group discussions, and reflection. The teacher also used heterogeneous group work, contextual case studies, educational correction, positive reinforcement, personal guidance, and communication with parents. The findings show that tolerance development in elementary students requires continuous planning, implementation, modeling, habituation, and evaluation. The study concludes that Pancasila Education can become an effective learning context for developing students’ tolerance when teachers connect Pancasila values with students’ daily classroom interactions.